On The Use of Non uniform inflow Model for Aerodynamics Analysis Helicopter Rotor Blade in the Forward Flight - Ghazirah, Ghazirah; Basuno, B.; Razali, Radzuan (2006)
The aerodynamics analysis of rotor blade helicopter in forward flight by using a non uniform inflow models are presented. This work can be considered as a continuation from the previous work as described in the Ref.1. Here the linear inflow model would be used as the basic idea in solving the aerodynamic problems oppose with the Ref. 1 which used a uniform inflow model. Physical flow phenomena around a rotor blade helicopter had been recognized very complicated. Rotor blade behaves like a finite wing. The presence of lift upon a finite wing would be followed by wake vortex sheet this vortex sheet promotes induced velocity along span wise non uniformly. Only certain wing plan form namely elliptic wing plan form could generate uniform induced velocity along span wise. For an arbitrary wing plan form the induced velocities were normally non uniform. The shape of wake vortex sheet released from a finite wing relatively simple, the vortex sheet can be considered as a plane of an infinitesimal thickness starting from the trailing edge line goes down in parallel to the free stream flow. In the case of the rotor helicopter, the rotor blade becomes a rotating lifting surface. As result the shape of wake vortex sheet becomes more complex than a fixed finite wing. Hence the non uniformity of the induce velocity become apparent.